Fraud adversely affecting the budget of the European Union: the forms, methods and causes - Zlata Djurdjevic
The paper analyses the forms, methods and causes of fraud that are perpetrated to the detriment of the budget of the European Union. The forms in which EU fraud appears are shown according to the criterion of kind of budgetary resource. Crime affecting the budgetary revenue of the EU tends to appear in the form of customs duty-evasion and false declarations concerning the customs-relevant information about goods. Crime adversely affecting the expenditure side of the EU budget appears in the form of subsidy fraud in the area of the Common Agricultural Policy, and subsidy fraud in the area of the structural policies. The methods used for the EU fraud committed and considered in the paper are document forgery, concealment of goods, corruption, violence and fictional business and evasion of the laws. In conclusion an explanation is given of the main exogenous criminogenic factors that lead to the EU frauds commonly perpetrated.EU fraud, customs duty-evasion, subsidy fraud, smuggling, methods of EU fraud, corruption, fictional business, etiology.